A comparative study on the effect of palladium dopant concentration on the photocatalytic properties of tin(IV) oxide / Amzamir Noor Kamarul Bahrin Noor and Dr. Vicinisvarri Inderan - Bahrin Noor, Amzamir Noor Kamarul; Inderan, Vicinisvarri (2020)
Several type of semiconductor photocatalysts such as TiO2, ZnO and SnO2 have been applied in treating dye containing wastewater. However, the application of SnO2 metal oxides as photocatalysts still remain limited despite the potential of the material to oxidize and degrade pollutant materials in wastewater. SnO2 can be modified with transition metal dopant such as palladium to improve its photocatalytic properties especially in the visible region of solar spectrum. In this work, SnO2 with different concentration of palladium dopant (0.5, 1, 3 and 5 mol%) were successfully analysed. The characterization data from X-ray diffraction (XRD), Fourier-Transform infrared spectroscopy (FTIR), high-resolution transmission electron microscopy with selected area electron diffraction (HRTEM-SAED), field emission scanning electron microscopy (FESEM) and UV-vis spectroscopy were carefully analysed and compared with previous studies. From XRD analysis, the results showed strong evidence of SnO2 nanoparticles formation. Whereas the FTIR peaks further confirmed the presence of the Sn-O bonds. The UV-vis result revealed the band gap of Sn-O considerably decreased from 3.75 eV to 3.66 eV with increasing Pd concentration. The selected 5 mol% Pd doped SnO2 was tested on photocatalyst reaction with methylene blue. In addition, the image of Pd doped SnO2 from HRTEM-SAED demonstrated the SnO2 nanoparticles existed in short nanorods in a closely packed structure. The comparison with literature review shows that Pd doping improve the photocatalytic properties of SnO2.